Prenatal diagnosis and molecular cytogenetic characterization of de novo distal 5p deletion and distal 22q duplication - Chih-Ping Chen; Jian-Pei Huang; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Wen-Lin Chen; Meng-Shan Lee; Wayseen Wang (Elsevier, 2020)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of de novo distal 5p deletion and distal 22q duplication. Case report: A 34-year-old woman was underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a derivative chromosome 5 [der(5)] with an abnormal distal 5p segment of unknown origin. The parental karyotypes were normal. Array comparative genomic hybridization (aCGH) analysis was performed on the cultured amniocytes, and the result was arr 5p15.33p13.3 (22,149-29,760,922) × 1.0, arr 22q13.2q13.33 (42, 192, 065-51,178,264) × 3.0 [GRCh37 (hg19)] with a 29.739-Mb deletion of 5p15.33-p13.3 encompassing 55 [Online Mendelian Inheritance in Man (OMIM)] genes including TPPP, TERT, SRD5A1, SEMA5A and CTNND2, and an 8.986-Mb duplication of 22q13.2-q13.33 encompassing 82 OMIM genes including TRMU, SCO2, TYMP, CPT1B and SHANK3. The fetal karyotype was 46,XY,der(5)t(5; 22)(p13.3; q13.2)dn. The pregnancy was subsequently terminated, and a malformed fetus was delivered with facial dysmorphism. Postnatal polymorphic DNA marker analysis confirmed a maternal origin of the aberrant chromosome 5. Conclusion: aCGH and polymorphic DNA marker analyses can determine the nature and parental origin of the de novo chromosome aberration, and the information acquired is useful for genetic counseling. Keywords: 5p deletion, 22q duplication, Prenatal diagnosis